Mention of the Prophets in Bang-e-Dara (In the Light of Archaic Poetry of Bang-e-Dara) - Basit, Abdul; Imtiaz, Muhammad; Humayun, Mian (sourcecoder, 2023)
Bang-e-dara is the first and most famous book of Iqbal’s poetry, in which he has mentioned the phenomena of the universe, philosophical concepts and ideas, famous personalities of ancient times, Muslim and non-Muslim conquerors, and Muslim kings of the Pak-o-Hind subcontinent. In addition, the greatness of the Muslims the fine art, magnificent buildings and a rich narrative of the glorious past of Muslims. Along with many Prophets, many Muslim and non-Muslim religious leaders are also mentioned in this book. However, this research article also includes the poetry of Iqbal which is not included in Bang-e-Dara and as it was included in the category of archaic poetry. The detailed work in this regard can be seen in my research thesis.In the article under consideration, the mention of the Prophets is included along with the marking of Bang-e-Dara’s poems with footnotes and comments.